3D Printers for Food Printing – Advantages and Drawbacks of Market Ready Technical Solutions - Harasym, Joanna (Drukarki 3D do druku żywności – zalety i wady rynkowych rozwiązań technicznych, 2022)
The article takes a closer look at the basics of food 3D printing techniques in order to point out the real problems of this technology, especially through the perspective of the latest technical solutions (3D printers) available on the market in 2022. Food 3D printing technique is attracting the interest both in research and on the market. In the case of food, the most common technique used is paste extrusion, in which the material is placed in a syringe-shaped container and extruded while the print head moves and puts on the layers one by one, reproducing the final shape. Although research has been done on other additive processes, such as binder jetting and selective laser sintering using powdered food products, it is still debatable whether these processes are feasible for food printing.
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2022, Nr 38, s. 41-59
Keywords: additive printing; 3D printing; food; extrusion; 3D food printer; druk addytywny; druk 3D; żywność; ekstruzja; drukarka 3D żywności